2020
DOI: 10.1002/aenm.202002199
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Etching of Layered Double Hydroxide Nanosheets for Enhanced Photocatalytic N2 Reduction to NH3

Abstract: Layered double hydroxide (LDH) nanosheets show good activity in a wide range of photoreactions, with this activity being generally attributable to an abundance of surface oxygen vacancies or coordinatively unsaturated metal cations in the nanosheets which serve as active sites for reactant adsorption and activation. Recently, LDH nanosheets have been shown to be very effective for photocatalytic N2 reduction to NH3 using water as the reducing agent. Herein, it is demonstrated that a simple pretreatment of ZnCr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
149
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(152 citation statements)
references
References 45 publications
1
149
1
1
Order By: Relevance
“…Most research reports on the selectivity and conversion rate of photocatalytic N 2 reduction are relatively low, and the output of ammonia is usually low. [214,215] Therefore, in the experiment of photocatalytic N 2 reduction to produce NH 3 , the ammonia produced is not necessarily produced by dinitrogen reduction, and it may also come from other pollutants, such as ammonia, nitrogen oxides, and nitrates contained in air, nitrogen flow, and catalyst itself. Therefore, it is necessary to perform a series of control experiments to ensure that the N in the production of NH 3 comes from N 2 , rather than accidental pollution.…”
Section: Rigorous Protocols and Accurate Determination Of Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Most research reports on the selectivity and conversion rate of photocatalytic N 2 reduction are relatively low, and the output of ammonia is usually low. [214,215] Therefore, in the experiment of photocatalytic N 2 reduction to produce NH 3 , the ammonia produced is not necessarily produced by dinitrogen reduction, and it may also come from other pollutants, such as ammonia, nitrogen oxides, and nitrates contained in air, nitrogen flow, and catalyst itself. Therefore, it is necessary to perform a series of control experiments to ensure that the N in the production of NH 3 comes from N 2 , rather than accidental pollution.…”
Section: Rigorous Protocols and Accurate Determination Of Ammoniamentioning
confidence: 99%
“…In addition, the detection of product NH 3 also requires careful selection of appropriate detection methods. Commonly used ammonium detection methods include: ion chromatography, [214,220] colorimetry (indophenol blue method and Nessler's reagent), [221][222][223][224] 1 H NMR spectroscopy, [225] and ammonia ion selective electrodes. [226] For aqueous ammonia solutions, these methods have shown higher accuracy in a wide range of ammonia concentrations.…”
Section: Rigorous Protocols and Accurate Determination Of Ammoniamentioning
confidence: 99%
“… 3 11 Among various solar energy conversion techniques, photocatalysis is deemed as a promising, environmentally benign, and cost-effective strategy to generate both fuels and high-value chemicals. 12 18 During the past decades, numerous studies have been focused on several well-known reactions (e.g., H 2 production, 19 26 N 2 fixation 27 30 and CO 2 conversion 31 34 ) achieved via photocatalysis. Recently, a range of emerging photocatalytic reactions generating fuels and/or valuable chemicals has been attracting increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…This efficient charge transfer inhibits the recombination of charge carriers, which is beneficial to improve catalytic performance. It is reported that there are large number of surface oxygen vacancies or coordinated unsaturated metal cations in LDH, which can serve as active sites for the adsorption and activation of reactants, thus offering good catalytic activity [116–118] . Scientists may develop abundant materials; for example, hematite can realize non‐directional aromatic C−H amination.…”
Section: Catalyst Electrode and Electrolyzermentioning
confidence: 99%